Crítica às políticas criminais de drogas à luz dos princípios constitucionais penais no estado democrático de direito - Ramos, Ana Flávia Jordão (2010)
This dissertation presents as thematic the public and criminal policies about illicit drugs consolidated in the Brazilian legal system. It will be made a critical analysis on the compatibility among the policies on drugs and the constitutional principles of the criminal law in the Democratic State under the rule Law. Due to complexity of social factors that guide the subject, a interdisciplinary approuch will be used, including theorical references of Law and sociological sciences, in onder to establish coherent bonds between those ones. The methodology consists in the bibliographical research of national and foreign sources, the search of data collected in official institutions, and finally, the study of sentences pronounced by the Brazilian Superior Tribunal Federal and of the argentinian Supreme Court. In the theoretical field, it focus in the reasons that justify the ambivalent treatment between dealers and users, as well as the social labelling that represents them. The principles of the Contemporary criminal law will be established as limits to the exercise of the social control by the State, considering the presence of new risks and the consequent expantion of the criminal norm. From there, it Will be developed a study about the preventive and symbolic functions of the criminal law in the contemporary society, especially, about the aspects involving the use of illicit drugs and the traffic s repression. This paper debates the functions of the criminal law in the democratic State undes the rule of Law and establishes the limits to the criminalization of behaviors under the principles of the minimum intervention and ofensivity. After trace these limits, it will be criticize the aspects of the criminal politics that are incompatible with the task of the contemporary criminal Law in order to demonstrate that the international policies of drugs imposes the criminalization of behaviors without considering the local features. This facts implies in the transference to the countries classified as as of transit and producers of the responsibility for the combat to the drug trafficking and in the inefficacy of the directed policies of public health to the consumer by the National System of Public Policies on Drugs (SISNAD).